Microencapsulation of a Colombian Spodoptera frugiperdaNucleopolyhedrovirus with Eudragit® S100 by spray drying - Camacho Kurmen,Judith Elena (2015)
A Colombian Spodoptera frugiperda nucleopolyhedrovirus NPV003 with high potential for the development of an efficient biopesticide was microencapsulated by spray drying with a pH dependent polymer (Eudragit® S100). Conditions for microparticles production were standardized and microencapsulation process was validated. Physical properties, insecticide activity and photo-stability of microencapsulated virus were determined. The microparticles were spherical and irregular shaped, with sizes between 17.64 and 19.47 µm. Moisture content was 10.38 ± 0.87%; encapsulation efficiency 84.61± 13.09% and process yield was 91.20 ± 6.40%. Microencapsulation process did not affect viral insecticidal activity and provided efficient protection against UVB radiation. Results demonstrated technological feasibility of spray drying process to be used in formulating a biopesticide based on NPV003.